2021
DOI: 10.1002/smll.202101483
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide Nanosheets Interact and Interfere with SARS‐CoV‐2 Surface Proteins and Cell Receptors to Inhibit Infectivity

Abstract: Nanotechnology can offer a number of options against coronavirus disease 2019 (COVID‐19) acting both extracellularly and intracellularly to the host cells. Here, the aim is to explore graphene oxide (GO), the most studied 2D nanomaterial in biomedical applications, as a nanoscale platform for interaction with SARS‐CoV‐2. Molecular docking analyses of GO sheets on interaction with three different structures: SARS‐CoV‐2 viral spike (open state – 6VYB or closed state – 6VXX), ACE2 (1R42), and the ACE2‐bound spike… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
82
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(87 citation statements)
references
References 90 publications
(104 reference statements)
5
82
0
Order By: Relevance
“…Research on graphene-based nanomaterials has boomed in biomaterial applications over the past few years. With outstanding physical, chemical and biological properties, graphene is considered to be revolutionary material and shows great potential for applications in tissue regeneration, drug delivery and other biomedical areas (Hu et al, 2020;Fu et al, 2021;Unal et al, 2021). Therefore, the purpose of this review is to highlight the scientific progress over the years and further summarize the physical and chemical properties, family members and applications in bone tissue engineering of this graphene-based nanomaterial.…”
Section: Introductionmentioning
confidence: 99%
“…Research on graphene-based nanomaterials has boomed in biomaterial applications over the past few years. With outstanding physical, chemical and biological properties, graphene is considered to be revolutionary material and shows great potential for applications in tissue regeneration, drug delivery and other biomedical areas (Hu et al, 2020;Fu et al, 2021;Unal et al, 2021). Therefore, the purpose of this review is to highlight the scientific progress over the years and further summarize the physical and chemical properties, family members and applications in bone tissue engineering of this graphene-based nanomaterial.…”
Section: Introductionmentioning
confidence: 99%
“…In this kit, MNPs are used to capture and concentrate the viral-RNA from the COVID patient's sample (DST 2020). Chitosan (CH) and GO are found significant in inhibiting and detecting SARS-CoV-2 [14][15][16][17]. CH, a naturally abundant cationic polymer is insoluble in an aqueous medium but soluble in a weakly acidic medium [18].…”
Section: Introductionmentioning
confidence: 99%
“…Graphene and its derivatives too have a lot to offer against COVID-19, attributing to their unique properties like thermomechanical durability, piezoelectricity, large-surface area, strong antiviral potency, and so on [21,22]. Graphene derivative GO with the abundance of oxygen-containing -OH, carbonyl (C=O), epoxide, and -COOH functional groups on its basal planes and availability of strong negative surface charge can be used to fabricate better RNA extracted protocol against SARS-COV-2 [17,4]. Among MNPs, ceramics (spinel ferrites, (SFs)) have allured substantial interest attributing to their unusual physicochemical characteristics [23].…”
Section: Introductionmentioning
confidence: 99%
“…Kleinet et al concluded that their protocol is suitable for RNA extraction of any type of virus from pharyngeal swabs [ 15 ]. Chitosan (CH) and GO are found significant in inhibiting and detecting SARS-CoV-2 [ 16 19 ]. CH, a naturally abundant cationic polymer, is insoluble in an aqueous medium but soluble in a weakly acidic medium [ 20 ], majorly consisting of -NH 2 and hydroxyl (–OH) groups, where –NH 2 group gets converted into soluble –NH 3 + [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Graphene and its derivatives too have a lot to offer against COVID-19, attributing to their unique properties like thermomechanical durability, piezoelectricity, large surface area, strong antiviral potency, and so on [ 23 , 24 ]. Graphene derivative GO with the abundance of oxygen-containing –OH, carbonyl (C=O), epoxide, and –COOH functional groups on its basal planes and availability of strong negative surface charge can be used to fabricate better RNA-extracted protocol against SARS-COV-2 [ 4 , 19 ]. Among MNPs, ceramics (spinel ferrites (SFs)) have allured substantial interest attributing to their unusual physicochemical characteristics [ 25 ].…”
Section: Introductionmentioning
confidence: 99%